Video fluorescence microscopy studies of phospholipid vesicle fusion with a planar phospholipid membrane. Nature of membrane-membrane interactions and detection of release of contents (The Rockefeller University Press, 1987)
Video fluorescence microscopy was used to study adsorption and fusion of unilamellar phospholipid vesicles to solvent-free planar bilayer membranes. Large unilamellar vesicles (2-10 microns diam) were loaded with 200 mM of the membrane-impermeant fluorescent dye calcein. Vesicles were ejected from a pipette brought to within 10 microns of the planar membrane, thereby minimizing background fluorescence and diffusion times through the unstirred layer. Vesicle binding to the planar membrane reached a maximum at 20 mM calcium. The vesicles fused when they were osmotically swollen by dissipating a KCl gradient across the vesicular membrane with the channel-forming antibiotic nystatin or, alternatively, by making the cis compartment hyperosmotic. Osmotically induced ruptures appeared as bright flashes of light that lasted several video fields (each 1/60 s). Flashes of light, and therefore swelling, occurred only when channels were present in the vesicular membrane. The flashes were observed when nystatin was added to the cis compartment but not when added to the trans. This demonstrates that the vesicular and planar membranes remain individual bilayers in the region of contact, rather than melding into a single bilayer. Measurements of flash duration in the presence of cobalt (a quencher of calcein fluorescence) were used to determine the side of the planar membrane to which dye was released. In the presence of 20 mM calcium, 50% of the vesicle ruptures were found to result in fusion with the planar membrane. In 100 mM calcium, nearly 70% of the vesicle ruptures resulted in fusion. The methods of this study can be used to increase significantly the efficiency of reconstitution of channels into planar membranes by fusion techniques.